Prevalence and Molecular Characterization of Helicobacter pylori in Patients with Chronic Diarrhea in Thi-Qar Province - Hussain Adnan Hashim; Mohammed Mahdi Abd (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Helicobacter pylori is a globally prevalent bacterial pathogen increasingly linked to gastrointestinal and extra-gastric disorders. Specific Background: Its role in chronic diarrhea remains insufficiently characterized in Iraq, particularly in Thi-Qar Province, where epidemiological data are inconsistent. Knowledge Gap: Limited molecular evidence exists on local H. pylori strains and the performance of diagnostic methods in patients with chronic diarrhea. Aims: This study aimed to determine the prevalence of H. pylori and characterize circulating strains among chronic diarrhea patients using stool antigen testing and PCR targeting the cagA gene. Results: A high prevalence was detected by antigen testing, while PCR revealed lower positivity, and two local cagA-positive isolates were genetically characterized and registered in GenBank. Novelty: The study reports the first molecular registration of H. pylori strains from chronic diarrhea cases in Thi-Qar Province. Implications: These findings underscore diagnostic variability and highlight the relevance of local molecular data for epidemiological surveillance and future clinical research.Keywords : Helicobacter pylori, chronic diarrhea, stool antigen test, PCR detection, molecular characterizationHighlight : Rapid stool antigen testing revealed high Helicobacter pylori detection among chronic diarrhea patients. PCR targeting cagA gene showed substantially lower positivity, indicating diagnostic sensitivity variation. Genetic sequencing identified distinct local strains registered in international genomic databases.